An evaluation for anthrax disease control program in Gunungkidul District 2020 - Asmi Rizal Abdillah (Berita Kedokteran Masyarakat, 2021)
Objective: Anthrax disease is one of the infectious diseases that can cause outbreaks and spread throughout the world, including Indonesia. Gunungkidul is one of the districts in Yogyakarta Province whose status is endemic to anthrax disease. The largest anthrax in humans ever in Gunungkidul District were anthrax cases in December 2019 with 111 people (probable and confirmed cases). The evaluation program to identify the implementation of the anthrax disease control program on input, process, and output aspects in the Gunungkidul district in 2020.Method: The evaluation design used descriptive study. Evaluation of the program was conducted in January-March 2021 at 30 community health centers and one health office. The evaluated subjects were zoonotic program holder officers in each community health center and health office. We use a checklist and questioner to collect data.Results: The weakness of input aspect: only (70%) community health centers that have Guidelines for the management of anthrax cases and only (36.7%) Standard Operating Procedure (SPO). Process aspect: recording and reporting of anthrax cases only done if the case is a case of confirmation, the implementation of disease socialization activities that have not maximized (73.33%), the absence of slaughterhouse as one form of supervision of livestock slaughter, feedback given by the health service to the health center (81.25%). Output aspect: The overall strengthening of human resources that has been conducted is a cross-sector and cross-program meeting post-anthrax event in 2019. The zoonotic training program holder officers have participated in is only (10%) of the total community health centers.Conclusion: Strengthening human resources across sectors and programs. Create a slaughterhouse for surveillance measures against the slaughter of livestock. Hopefully, the programs can improve the early detection of anthrax disease.